2016
DOI: 10.1186/s12870-016-0782-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wheat microspore embryogenesis induction by transcriptome and small RNA sequencing using the highly responsive cultivar “Svilena”

Abstract: BackgroundMicrospore embryogenesis describes a stress-induced reprogramming of immature male plant gametophytes to develop into embryo-like structures, which can be regenerated into doubled haploid plants after whole genome reduplication. This mechanism is of high interest for both research as well as plant breeding. The objective of this study was to characterize transcriptional changes and regulatory relationships in early stages of cold stress-induced wheat microspore embryogenesis by transcriptome and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 55 publications
6
63
1
Order By: Relevance
“…Retaining the somatic molecular features suggests that cell fate transition is not completed at the microspore stage. Together with the cytological observation that the microspore can be dedifferentiated and generates a somatic embryo in vitro (Segui-Simarro and Nuez, 2007;Daghma et al, 2014;Seifert et al, 2016), these findings indicate somatic fate and a potential pluripotent state of the microspore at the molecular level.…”
Section: Reprogramming Gene Expression and Sc Lineage Developmentmentioning
confidence: 56%
See 1 more Smart Citation
“…Retaining the somatic molecular features suggests that cell fate transition is not completed at the microspore stage. Together with the cytological observation that the microspore can be dedifferentiated and generates a somatic embryo in vitro (Segui-Simarro and Nuez, 2007;Daghma et al, 2014;Seifert et al, 2016), these findings indicate somatic fate and a potential pluripotent state of the microspore at the molecular level.…”
Section: Reprogramming Gene Expression and Sc Lineage Developmentmentioning
confidence: 56%
“…The microspore retains the molecular features of somatic cells A microspore is cytologically considered a type of pluripotent cell that develops into an embryo-like structure upon stress or hormone induction (Honys and Twell, 2004;Segui-Simarro and Nuez, 2007;Daghma et al, 2014;Seifert et al, 2016); however, molecular evidence supporting this concept is still limited. Principal component analysis (PCA) and correlation matrix analysis showed that the mRNome of the microspore is closer to that of callus (r = 0.71), leaf (r = 0.65) and pistil (r = 0.72) than that of the GC (r = 0.46), SCs (r = 0.35) and MPG (r = 0.40) (Figures 2a and S2a, Table S5).…”
Section: Long Non-coding Rnas Are Abundantly Expressed In Individual mentioning
confidence: 99%
“…agropec. bras., Brasília, v.53, n.5, p.575-582, May 2018 DOI: 10.1590/S0100-204X2018000500006 like feature, which has been previously reported as a representative morphology of totipotent cells (Seifert et al, 2016). Immediately after this phase, the first divisions were observed, although, in most genotypes, it occurred 20 days post-incubation.…”
Section: Resultsmentioning
confidence: 66%
“…For example in Brassicas, microspore mutation studies have enabled modifications of disease resistance, cold tolerance, and fatty acid composition [43]. Additionally, in vitro microspore culture systems have allowed for detailed study of embryogenesis, early cell fate decisions, embryogenesis, and totipotency [44][45][46]. All of these applications of haploid and DH techniques, as well as many others not mentioned here, could confer the same benefits to perennial ryegrass breeding and research as they have done, and currently do, in species for which effective and efficient DH induction protocols are available [14].…”
Section: Haploids and Doubled Haploids: Their Production And Use In Bmentioning
confidence: 99%